Design a medical device for blood oxygen concentration and temporal heart beat rate - Myint, Cho Zin; Barsoum, Nader; Wong, Kiing Ing (Inderscience Enterprises Limited, 2011)
The wireless network technology is increasingly important in healthcare as a result of the aging population and the tendency to acquire chronic disease such as heart attack, high blood pressure amongst the elderly. The elderly do not have to show up to the hospital for a blood pressure check. It can be done while they are working by wearing wireless sensor device at home. A wireless sensor network system that has the capability to monitor physiological sign such as SpO2; saturation of arterial oxygen and heartbeat rate in real-time from the human body is highlighted in this study. This research is to design a prototype snesor network hardware, which consists of microcontroller PIC18F series and transceiver unit. The sensor is incorporated into a wearable body sensor network which is small in size and easy to use. The sensor allows a non-invasive, real time method to provide information regarding the health of the body. This kind of medial application such as wireless sensor network has a promising future for humankind. This enables a more efficient and economical means for managing the healthcare of the population.